Pengaruh Fitur Live Shopping, Interaksi Host, dan Diskon Terhadap Keputusan Pembelian Konsumen Generasi Z di Tiktok di Wilayah Solo Raya - Syifa Permata Nindiyasti; Ari Susanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study examines the influence of live shopping features, host interactions, and discounts on purchasing decisions of Generation Z users on TikTok in the Solo Raya region. Using a quantitative methodology, this study collected data through a survey of 100 Generation Z participants who had completed dare transactions using TikTok's live shopping option. Researchers analyzed the data using SPSS software, including checking the validity and reliability of the instrument, assessing classical assumptions, and testing hypotheses. The study findings indicate that host interactions and discounts significantly influence purchasing decisions, while the live shopping feature showed no significant effect. The adjusted R-squared value of 0.228 indicates that this third variable contributes 22.8% of the variability in purchasing decisions, with the remaining 77.2% being caused by external factors